Mitochondria in health and disease - Maher, Eamonn (Henry Stewart Talks, 2020)
Mitochondria: structure, function, biogenesis, and biochemistry, The mitochondrial genome, Inheritance of mitochondrial disorders and reproductive options, Mitochondrial heteroplasmy, The reproductive aspects of mitochondrial disease, Clinical features of mitochondrial disease